Nigrospora weininensis sp. nov., a new potent nematicidal fungus isolated from Globodera rostochiensis in Guizhou, China - Liu, Mingrui; Liu, Yufeng; Zhang, Xinyue; Wu, Yan; Wang, Yong; Norphanphoun, Chada; Nizamani, Mir Muhammad; Yang, Maofa; Wijayawardene, Nalin; Hu, Jifeng; Li, Kaihuai; Yang, Zaifu (Phytotaxa, 2024)
Three Nigrospora strains were isolated from cysts of the nematode, Globodera rostochiensis in Guizhou, China. This study identified and characterized the strains through morphological traits and phylogenetic analyses of internal transcribed spacer (ITS), elongation factor 1-alpha (tef1α), and beta-tubulin (β-tubulin) loci, which confirmed that the strains belonged to a new species described as Nigrospora weininensis. Pre-experiments showed that they might have nematicidal activity. This was evaluated and the fermentation broth produced by the fungus showed mortality rates of 100% after 48 h against Aphelenchoides besseyi, Bursaphelenchus xylophilus, and Ditylenchus destructor.